Exploring the attitudes of bottled wine distributors toward wine producers in the Portuguese wine sector - da Cunha, N. P.; Loureiro, S. M. C.; Rego, A. (Journal of International Food and Agribusiness Marketing, 2015)
The wine sector has unique features that have not been deeply studied. This study aims to explore the attitudes of bottled wine distributors toward wine producers in the Portuguese wine sector. Eleven interviews (about 60 min each) were carried out with all major wine distributor managers. The transcribed interviews were analyzed using qualitative software. Content analysis shows that distributors develop six main attitudes toward producers: (a) Long-term Relationship, (b) Cooperation, (c) Interdependence, (d) Product Quality, (e) Trust, and (f) Brand Image. Findings may help managers of the wine sector and promote favorable relationships with the distributing customers.